The festivities of san pacho in quibdó (chocó, colombia) as a tool for community organizing (2010)
The diversity and richness of the culture from Chocó is evident in its wide variety of representative elements as chirimías (‘bagpipes’). This article shows the role of festivities in honor of St. Francis of Assisi, in which community organizations are promoted and built, and processes of solidarity, responsibility and resistance are reflected. These strengthen the cultural identity in the context of the problems faced by the inhabitants of Chocó